2009
DOI: 10.1055/s-0029-1217989
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Practical Synthesis of Sulfonyl Chlorides from Thiol and Disulfide Derivatives

Abstract: Hydrogen peroxide, in the presence of zirconium tetrachloride, is a very efficient reagent for the direct oxidative conversion of thiol and disulfide derivatives into the corresponding sulfonyl chlorides with high purity through oxidative chlorination. Excellent yields, very short reaction times, mild reaction conditions, and the avoidance of harsh reagents are the main advantages of this method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 4 publications
(4 reference statements)
0
13
0
Order By: Relevance
“…20 We were delighted to find that conversion of 3 to 4 occurred rapidly at room temperature (under 5 min) with quantitative conversion. However, it should be noted that a large exotherm in the region of +30 °C (Caution!)…”
Section: Scheme 1 Sandmeyer Approach Tomentioning
confidence: 99%
“…20 We were delighted to find that conversion of 3 to 4 occurred rapidly at room temperature (under 5 min) with quantitative conversion. However, it should be noted that a large exotherm in the region of +30 °C (Caution!)…”
Section: Scheme 1 Sandmeyer Approach Tomentioning
confidence: 99%
“…Once all of the solid had dissolved, rapid stirring is commenced (>800 rpm) and the reaction mixture is cooled to ambient temperature, during which time the desired product precipitates as colorless crystals. The reaction mixture is then cooled in an ice-water bath to 0 °C and stirred for a further 2 h. The precipitate is then collected by vacuum-filtration (375 mmHg) onto a 250 mL sintered-glass funnel, washed with two portions of hexane (2 x 57 mL) (Note 17) and allowed to dry under vacuum to give analytically pure S-(4-cyano-2-methoxyphenyl)dimethylcarbamothioate (2) (23.8 g, 85%) ( Notes 18,19,and 20).…”
Section: Figure 1 Reaction Assembly For Step a A: Reaction During Dmentioning
confidence: 99%
“…Bahrami reported that the oxidative chlorination of aryl and alkyl thiols and disulfides with hydrogen peroxide and zirconium(IV) chloride proceeded rapidly to give sulfonyl chlorides in high yields and fast reaction times. 20 We were delighted to find that conversion of 3 to 4 occurred rapidly at room temperature (under 5 min) with quantitative conversion. However, it should be noted that a large exotherm in the region of +30 °C (Caution!)…”
Section: Scheme 1 Sandmeyer Approach Tomentioning
confidence: 99%
“…Given their importance in various fields, there is a strong interest in developing efficient synthetic methods for preparing them. The oxidative chlorination of thiols has been a frequently applied synthetic pathway using several combinations of oxidants and chloride sources [21][22][23][24][25][26][27][28]. In addition, chlorination with different sulfur compounds [29][30][31][32] or Grignard reactions [33] have been developed as efficient methods for the synthesis of sulfonyl chlorides.…”
Section: Introductionmentioning
confidence: 99%